Inorganic fraction of oil sands process-affected water induces mammalian macrophage stress gene expression and acutely modulates immune cell functional markers at both the gene and protein levels. (August 2020) - Phillips, Nicole A.I.; Lillico, Dustin M.E.; Qin, Rui; McAllister, Mark; El-Din, Mohamed Gamal; Belosevic, Miodrag; Stafford, James L.
Abstract: The focus of the present study was to examine the acute immunotoxic properties of oil sands process-affected waters (OSPW) using the RAW 264.7 macrophage cell line. Specifically, we used a quantitative PCR assay to monitor changes in the expression of stress, cytokine, and antimicrobial enzyme genes in activated macrophages following acute (i.e. < 24 h) exposure of the cells to whole OSPW and its fractions. Overall, our data shows that OSPW inorganic fraction (IF) significantly induces the expression of genes associated with oxidative stress and DNA damage and that the OSPW-IF also significantly augmented cytokine gene expression. These effects are similar to what was observed following whole OSPW exposures, which contrasts the minimal effects observed when cells were treated with equivalent doses of the OSPW organic fraction (OF). Surprisingly, OSPW-IF had reciprocal effects on gene and protein expression levels of two key macrophage enzymes (e.g. inducible nitric oxide (iNOS) synthase and arginase), which indicates that components within OSPW-IF have the unique ability to alter the overall functional states of macrophage by polarizing them towards an alternatively activated status; concomitant with the reciprocal depression of iNOS levels and enhanced expression and activity of arginase. Collectively, these findings show that at sub-lethal exposure doses, the inorganic constituents of OSPW have significant immunotoxicological properties that could potentially affect innate cellular defense responses of exposed animals. Highlights: Macrophages represent effective biosensors for examining OSPW immunotoxicity. OSPW inorganics significantly alter macrophage stress gene expression levels. OSPW inorganics significantly alter macrophage cytokine gene expression levels. OSPW inorganics alter the functional states of activated macrophages.